Land grabbing and agribusiness in Argentina: five critical dimensions for the analysis of corporate strategies and its impacts over unequal actors - Sosa, Andrea Patricia (2022)
This paper critically analyses the complexity of the land grabbing phenomenon in Argentina. We study land grabbing processes linked to the expansion of agribusiness by focusing on corporate regionally extended land grabbers? strategies through five dimensions: (1) forms of control over land (and other resources) are not restricted to the formal acquisition of property, (2) the role of both national and foreign actors are essential in land grabbing dynamics, (3) land grabbing is not expressed exclusively by the scale of the area traded, (4) the current cycle of land grabbing is part of the convergence of multiple crises and (5) forms of political action are complex and involve diverse positioning. We conclude that land grabbing mechanisms unfold differently depending on the diversity of socio-spatial formations they encounter in each territory and that forms of political action ?from below? are complex and not restricted to overt conflict.